LUMINESCENT COMPOSITES ON THE BASE OF MICROCRYSTALLINE CELLULOSE: SYNTHESIS, FABRICATION AND PROPERTIES (Journal of Sciences & Technology, 2019)
The data on preparation, structure and morphology of cellulose-based composites, those have oxide component as filler are reported. It is shown that depending on raw materials origin and processing degree cellulose samples reveal various degree of crystallinity (in the range 64 – 77 %). Obtained composites reveal even lesser crystallinity degree ≈ 57%. Detailed analysis of surface morphology was performed with using of scanning electronic microscopy. It was found the studied samples contains plates with sizes ~ 20 – 50 μ those consist of close-packed grains of 5-10 μ size. In the case of composites some oxide nanoparticles (sizes up to 200 nm) were incorporated into grains of microcrystalline cellulose. It was established the luminescence properties of cellulose are dependent on type of plant raw materials as well as on processing methods. These factors have influence on luminescence intensity but profile of photoluminescence bands remains practically unchanged. Under excitation in 337-532 nm spectral region the composites that contain K2Eu(PO4)(MoO4) and LaVO4:Sm are characterized by intensive visible photoluminescence. Spectra of these PL depend on excitation wavelength.